Clinical, Dermoscopic and Histhopatological Findings in Diagnosis of Nevus Spilus - Amillia Risa; Ennesta Asri; Irdawaty Izrul; Alimudin Tofrizal (Health and Medical Journal, 2021)
Introduction: Nevus spilus (NS) are seen in 0.2% to 2.3% of the population and have 0,13% to 0,2% risk for malignant transformation. Clinical, dermoscopic, and histhopatological features were describe in this case report in order to be easily recognize NS. Although NS is a benign cutaneous anomaly it has potential malignant transformation and requires regular follow up. Case Report: A case of nevus spilus in 23 years-old female was reported. There were multiple asymptomatic brownish pigmented spots over brownish patch on left cheek which gradually increased in number and size since 1 year ago. Dermatologic state: brown macules and dark brown papules in a speckled, overlying background café au lait macule. Dermoscopy revealed reticular pattern in background light brown and dark reticuloglobular pattern in dark speckled. Histopathology showed elongation of rete ridges with grouping of melanocyte cells at the tip, and proliferation of nevus cells. Conclution: Patient was planned to treat with Nd-Yag laser.